Pengaruh Motivasi Kerja, Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan serta Dampaknya pada Kinerja Perusahaan (Studi kasus pada PT. Pei Hai International Wiratama Indonesia) - Brahmasari, Ida Ayu; Suprayetno, Agus (Jurnal Manajemen dan Kewirausahaan, 2009)
This research aims at analyzing the influence of job motivation, leadership, and corporate culture toward employee job satisfaction, and their impact to the corporate performance. The proposed hypotheses: The job motivation have significance influence to the employee’s job satisfaction, The leadership have significance influence to the employee’s job satisfaction, The organizational culture have significance influence to the employee’s job satisfaction, The work motivation have significance influence to the corporate performance, The leadership have significance influence to the corporate performance, The organizational culture have significance influence to the corporate performance, The employee’s job satisfaction have significance influence to the corporate performance. The result of the research has evidenced that job motivation, leadership, and organizational culture are significantly related to the employee’s job satisfaction. Leadership, however, is negatively related to the employee’s job satisfaction. Job motivation is not significantly related to the corporate performance influenced by the intervening variable is employee’s job satisfaction. Leadership and organizational culture are significantly related to the corporate performance. From this result, there are two main conclutions that can be drawn in this study. First, the job motivation can not be related directly to the corporate performance if it is not connected by the employee’s job satisfaction variable. And the second conclution is that the leaderhip is negatively related to the employee’s job satisfaction.